Robotic advanced hybrid coronary revascularization: Outcomes with two internal thoracic artery grafts and stentsCentral MessagePerspective - Husam H. Balkhy, MD; Sarah Nisivaco, MD; Hiroto Kitahara, MD; Abdulrahman AbuTaleb, MD; Sandeep Nathan, MD; Ibraheem Hamzat, BS (JTCVS Techniques)
Objective: Advanced hybrid coronary revascularization is the integration of sternal-sparing multivessel coronary artery bypass grafting and percutaneous coronary intervention in patients with multivessel coronary artery disease. We sought to review our advanced hybrid coronary revascularization experience over an 8.5-year period using robotic totally endoscopic coronary artery bypass with bilateral internal thoracic artery grafts and percutaneous coronary intervention. Methods: From August 2013 to February 2022, 664 patients underwent robotic totally endoscopic coronary artery bypass at our institution. Of the 293 patients who underwent totally endoscopic coronary artery bypass assigned to a hybrid revascularization strategy, 156 patients received bilateral internal thoracic artery grafts and are the subject of this review. Patients underwent percutaneous coronary intervention with drug-eluting stents before or after totally endoscopic coronary artery bypass. We reviewed early and midterm outcomes (up to 8 years) in this cohort of patients with intent-to-treat advanced hybrid coronary revascularization. Results: The mean age of patients was 65 ± 10 years. The mean Society of Thoracic Surgeons predicted risk of mortality was 1.26 ± 1.56. Triple-vessel disease occurred in 94% of patients, and 17% of patients had 70% or more left-main disease. The mean operative time was 311 ± 54 minutes, and the mean hospital length of stay was 2.7 ± 1.1 days. All patients had bilateral internal thoracic artery grafts; the total number of grafts was 334. Eight seven percentage of patients had totally endoscopic coronary artery bypass ×2, and 13% of patients had totally endoscopic coronary artery bypass ×3. One patient received totally endoscopic coronary artery bypass ×4. The mean number of grafts per patient was 2.14 ± 0.4, and the mean number of vessels stented was 1.23 ± 0.5. There were no conversions, perioperative stroke, or myocardial infarction. Early mortality occurred in 2 patients. Early graft patency was 98% (209/214 grafts); left internal thoracic artery to left anterior descending patency was 100% (66/66 grafts). At 8-year follow-up in 155 patients (mean 39 ± 26 months), all-cause and cardiac-related mortality were 11.6% and 3.9%, respectively. Freedom from major adverse cardiac/cerebrovascular events including repeat revascularization was 94%. Conclusions: In patients with multivessel coronary artery disease, integrating robotic totally endoscopic coronary artery bypass with bilateral internal thoracic artery and percutaneous coronary intervention resulted in excellent early and midterm outcomes. Further studies are warranted.